“Your brother is compelled–not a hero!” - Imene Medfouni (L’Année du Maghreb)
Despite the “perpetual” implementation of the Arabisation policy in Algeria, French remains the de facto medium of instruction (MOI) in scientific courses in Algerian universities. The complex nature of MOI policy in Algeria calls for the need to explore not only the top-down perspective but also stakeholders’ views of teaching or studying in French. This research, therefore, aims to explore students’ and teachers’ attitudes towards French as a MOI in Algerian scientific university courses. Data was collected using interviews, questionnaires, and focus groups from three universities: the University of Annaba, the University of Batna, and the University of Oum El Bouaghi. While participants, particularly students, showed moderate satisfaction with French being the MOI, French scored very low when students and teachers were given a choice of the preferred MOI. The acceptance of French being the MOI is a way of accommodating reality; hence, it is seen as inevitable, as exemplified in one of the participants’ use of the expression “your brother is compelled–not a hero!” Students and teachers’ refusal of French does not reflect their actual need for a radical language policy change but their hope for amplifying their unheard voices through using the English language or the government’s political discourses of decolonizing Francophone education via Arabisation, reflecting the constant disputes between top-down policies and bottom-up stakeholders’ perspectives. Students–especially female students–were bound with French, despite their struggle of exclusion and failure, viewing this language as the only key to their success and integration in their Francophone context. The discrepancies among universities also shaped attitudes towards French, demonstrating the central or peripheral linguistic and historical variations in Algeria. These disparities highlight the need for an all-encompassing approach to address the various Algerian interlocutors (students, teachers, gender inequality, and university disparities) in policy-making.